Lorentz–Doppler profiles of hydrogen/deuterium lines for magnetic fusion: analytical solution for any angle of observation and any magnetic field strength. (20th December 2017) - Sanders, P; Oks, E
Abstract: We extend the analytical results for the Lorentz–Doppler profiles of highly-excited hydrogen/deuterium spectral lines for the arbitrary strength of the magnetic fieldB, obtained in a paper by one of us, Oks (2015 J. Quant. Spectr. Rad. Transfer 156 24), for observations parallel or perpendicular with respect toB, to arbitrary angles of the observation ψ . We study the evolution of the effect of the suppression of the π -components (compared to the σ -components) as the angle of the observation ψ decreases from 90°, i.e., as ψ decreases from the value, at which this counterintuitive effect was discovered in the paper quoted above. We show that the suppression of the π -components (compared to the σ -components) occurs at the perpendicular or close to the perpendicular direction of observation (with respect to the magnetic fieldB ), but disappears at lower values of the angle of the observation. Our results should be important, e.g., for spectroscopic diagnostics of edge plasmas of various magnetic fusion devices around the world. Another finding is that the width of the Lorentz–Doppler profiles is a non-monotonic function of the magnetic field for observations perpendicular toB, which is yet another counterintuitive result.